The influence of parental smoking and family type on saliva cotinine in UK ethnic minority children: a cross sectional study - Harding Seeromanie; Whitrow Melissa J; Maynard Maria J (BMC Public Health, 2010)
Abstract Background In the United Kingdom, there has been an increase in cigarette smoking in ethnic minority adults since the 1970s; in some groups levels are now similar to that of White British people. We aimed to examine the determinants of exposure to secondhand smoke in ethnic minority children. We hypothesised that exposure to secondhand smoke in children will vary across ethnic groups, but that the correlates of exposure would be similar to that of Whites. Methods The Determinants of Adolescent Social well-being and Health sample comprises 3468 White United Kingdom and ethnic minority (Black Caribbean, Black African, Indian, Pakistani, Bangladeshi) pupils aged 11-13 yrs. Outcome was saliva cotinine concentration. Explanatory variables collected by self-complete questionnaire included ethnicity, child reported household smoking and socio-economic circumstances. Data were analysed using linear regression models with a random intercept function. Results Ethnic minority children had lower saliva cotinine than Whites, partly explained by less smoking among parents. White and Black Caribbean children had higher cotinine levels if they lived in a household with a maternal smoker only, than with a paternal smoker only. Living in a lone compared to a dual parent household was associated with increased cotinine concentration of 45% (95%CI 5, 99%) in Whites, 27% (95%CI 5,53%) in Black Caribbeans and 21% (95%CI 1, 45%) in Black Africans after adjusting for household smoking status. Material disadvantage was a significant correlate only for White children (40% (95%CI 1, 94%) increase in cotinine in least compared to most advantaged group). Conclusions Ethnic minority children were less exposed to secondhand smoke than Whites, but the variations within groups were similarly patterned. These findings suggest that it is important not to be complacent about low smoking prevalence in some minority groups.